Analysis of Household Food Security of Fishermen in Coastal Area, Bangil District, Pasuruan Regency - Desy Cahyaning Utami; Wenny Mamilianti (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2021)
The low income of fishermen makes it difficult to fulfill basic household food needs and non-food basic needs. The purpose of this study was to analyze the level of energy adequacy and the level of protein adequacy and identify the factors that affect the food security of fishermen's households. The first analysis was carried out descriptively by combining food expenditure and energy consumption indicators. The second analysis uses a logit model regression analysis. The analysis results show that the food security condition of fishermen's households is at the food shortage level of 43.34%. Fisherman households in the food insecurity criteria are 10%, and food security is 23.33%. It means that more than 60% of fishermen's household income is spent on food consumption. The low income received has resulted in fisherman households being unable to allocate food expenditures to meet the nutritional adequacy of their household. The factors that influence the food security of fishermen's households are the size of the household members, household expenditures, and the nutritional knowledge of housewives. Local governments should coordinate with other institutions to formulate policies and plans for economic development in coastal areas.